Dose distribution in boron neutron capture therapy for the treatment of brain cancer. (March 2020) - Pereira, Leandro O.; Freitas, Renato P.; Ferreira, Douglas S.; Felix, Valter S.; Gonçalves, Elicardo A.S.; Pimenta, André R.; de Sousa Dutra, Rafael; Xavier da Silva, Ademir
Abstract: This work presents a study of the influence of the field size of an epithermal neutron beam on the dose distribution in treatments with boron neutron capture therapy using an anthropomorphic voxel-based simulator. To calculate the doses in the tissues and organs of the head, the Monte Carlo N-Particle radiation transport code is used. The results suggest the possibility of using a beam of 6 cm in diameter for the treatment of tumours in the frontal lobe and parietal regions. With a beam of 10 cm in diameter, we could treat tumours located in the frontal lobe, parietal lobe and thalamus. The work also shows that the contribution of the secondary components (gamma rays, fast and thermal neutrons) in the calculation of the total dose can result in up to 15% of the dose in the tumour tissue, 68% of the dose in the healthy brain tissue and 87% of the dose in the non-cephalic regions. Highlights: Treatments with Boron Neutron Capture Therapy. Epithermal Neutron Beam. Computacional Simulation to Calculate Doses in Tissues and Organs of the Head by MCNP. Influence of the Field Size of an Idealised Beam of Neutrons in Treatments with BNCT.